Neuropsychological features of adolescents with Internet-addictive behavior - Malygin, V.L.; Merkurieva, Y.A. (Konsulʹtativnai͡a︡ psikhologii͡a︡ i psikhoterapii͡a, 2015)
The aim of this study was to investigate neuropsychological features of adolescents with the Internet-addictive behavior. The sample comprised 756 adolescents with 316 females (40,2%) and 340 males (59,8%). The mean age was 15,5 years. The main experimental group (42 adolescents) included only those respondents who had high levels of Internet addiction combined with the objective data from the questionnaire. The control group consisted of adolescents with no signs of Internet-dependent behavior of comparable age and sex (50 adolescents). The main group was formed by analyzing results of the IAD test (K. Young), the CIAS test (Chen) and objective data obtained from interviews with adolescents, their parents and teachers. Neuropsychological features revealed by conducting adapted neuropsychological test for adolescents (based on the Luria-90). Adolescents with Internet-addictive behavior significantly differ from healthy on indicators of functional disorders: attention, control and regulation of activities and mediated memorizing. Correlating this data with localization features, we note the functional weakness of hemispheric commissures and left anterior lobe and weakness of the first block of the brain (Luria). Adolescents with Internet-addictive behavior from the point of view of neuropsychology are characterized by functional disorders spatial praxis, attention, control and regulation of activity and mediated memorizing. Also they have functional weakness of hemispheric commissures and the first block of the brain. На данный момент исследования особенностей подростков с интернет-зависимым поведением продолжаются, и одним из направлений является исследование биологических предпосылок развития данного зависимого поведения. Исходя из того факта, что нарушение развития мозговых структур, а также их повреждение являются фактором риска для развития химической аддикции, мы предполагаем, что и в случае интернет-аддикции возможно найти нейропсихологические корреляты. Целью исследования было изучение нейропсихологических особенностей у подростков с интернет-зависимым поведением. Нами было обследовано 133 учащихся школ ЦАО г. Москвы, средний возраст 15.5 лет. Далее, по результатам методики «Шкала интернет-зависимости Чен» и экспертной оценки, данная группа была поделена на две группы: экспериментальную и контрольную. В экспериментальную группу вошли 98 испытуемых, в контрольную — 100. Нейропсихологические особенности выявлялись путем проведения адаптированного нейропсихологического исследования для подростков (на основе Лурия-90). Корреляционный анализ не выявил значимой корреляционной связи показателей (рd0,05), однако мы обращаем внимание на следующее: показатели функциональных нарушений правого полушария и межполушарных взаимодействий имеют тенденцию к корреляции. В ходе анализа различий выборок были выявлены следующие значимые различия: у подростков с интернет-зависимым поведением отмечаются более высокие показатели нарушений пространственного праксиса, слухомоторных координаций, опосредованного запоминания, контроля и регуляции деятельности, внимания. Соотнося эти данные с локализацией функций, мы отмечаем функциональную слабость межполушарных комиссур и левой передней доли, кроме того, учитывая утомляемость, снижение концентрации внимания, можно говорить о слабости первого блока мозга. Важно отметить, что функциональная недостаточность межполушарных взаимодействий увеличивает нагрузку на первый и третий блоки мозга.